Protecting the child's relationship with parents amid family disintegration: Visitation Rights – A legal and judicial approach - Ammari, Sana; Baha, Latifa (The International tax journal, 2025)
Visitation is among the most important rights that preserve a child's connection with their family environment. It helps maintain the child's identity and meet emotional and psychological needs that are essential for healthy development. To ensure this right, the legislator has established several safeguards. Chief among these is the requirement to consider the best interest of the child. The judiciary is entrusted with upholding and enforcing this interest within its broad discretionary powers. Following the divorce of parents, the child is often required to live with one of them due to the dissolution of the marital bond. If custody is granted to one parent, the other retains the right to visit the child. One of the essential aspects of the child's well-being is the continued connection with the non-custodial parent. Proper care is not complete without a reasonable degree of visitation and the involvement of both parents in the child's upbringing.